PENGARUH MEDIA MASSA TERHADAP PERKEMBANGAN PESERTA DIDIK - ABHANDA AMRA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
The rapid development of knowledge and technology brings learners to innovative things in their lives. Television is one of technologies lead learners to the positive things. For example, television could facilitate learners to study easily and enlarge their horizons. It, however, has a negative effect on learners’ personality. Learners assume that what they watch and listen are absolutely correct. As a result, they do all the things as what they watch. They are failed to filter the positive values on television. In order to anticipate these negative values, teachers should corporate to parents. Parents, for example, could empower leaner’s iman (faith), build their character values, and enrich their ibadah (worship) to God Almighty. By empowering parents, learner’s bad value could be minimized.Kata kunci: media massa, perkembangan, peserta didik